Can foreign ownership reduce bank risk? Evidence from Vietnam - Tu DQ Le (Review of Economic Analysis (REA), 2021)
This study investigates the impact of foreign ownership on bank risk in Vietnam between 2006 and 2015. Our findings show that foreign ownership can lower bank risk, suggesting that the State Bank of Vietnam should further remove restrictions on foreign investments in the banking system. The findings also indicate that higher bank risk is associated with greater technical efficiency, suggesting that the skimping-cost hypothesis may exist. The same conclusion is true for large banks, for banks with higher liquid assets and those with greater loan growth. Also, the findings demonstrate that assets diversity may reduce bank risk, suggesting that Vietnamese banks should diversify their assets from loans towards derivatives and other earning assets to improve banks' stability. Finally, our findings demonstrate that a less concentrated market can lower bank risk, suggesting that the future mergers and acquisitions in Vietnam that involve a state-owned commercial bank should be approached with caution.
Keywords: G21; 330; Bank risk; foreign ownership; market concentration; Vietnam; GMM